ANALISIS SURVIVAL TIME TO CLAIM PADA PRODUK ASURANSI JIWA BERJANGKA : STUDI KASUS PT XYZ - Jati, Muthaqin Dhamar Widhoro; Suardi, Lenny (MATHunesa: Jurnal Ilmiah Matematika, 2024)
This study aims to determine the duration of time to claim from policyholders of term life insurance products based on the characteristics of age, gender, marital status, premium amount, sum insured, insurance period and distribution channel using survival analysis. Survival data in this study is the policy period from the beginning of the observation period until the claim submission. By using term life insurance coverage data from 2018 to 2023 with a total of 6,070 data consisting of 632 claim data as claim occurrence data and 5,438 censored data. The method used in this study is nonparametric analysis in the form of Kaplan-Meier estimation (limit product estimation) to determine the survival probability of policyholders based on covariates that are thought to affect them. The semi-parametric analysis uses the Cox proportional hazard model to determine the relationship between the claim duration variable and the covariates in the model. The result of this study is that all covariates are significantly effect on claim duration and the best model obtained fulfil the proportional hazard assumption.Keywords: Term Life Insurance, Survival Analysis, Kaplan-Meier Estimation; Cox Proportional Hazard